The Influence of Interactive Learning Media on the Poetry Reading Ability - Gita Faradilla; Saprida; Asri Yulianda (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the effect of interactive learning media on the poetry reading ability of eighth-grade students. A quasi-experimental design with a pretest-posttest control group was applied, and the sample was selected using a purposive sampling technique. Data were collected through pretests and posttests, assessing students' fluency, expression, intonation, and comprehension in poetry reading. The results indicate a significant improvement in students' poetry reading ability after using interactive learning media. The average pretest score of 58.59 increased to 67.18 in the posttest, showing a notable enhancement in performance. Statistical analysis using a t-test yielded a t-count value of 7.857, which exceeded the t-table value of 2.353, confirming a significant effect. These findings demonstrate that interactive learning media effectively enhances students’ engagement and performance in poetry reading. The study concludes that interactive learning media is a valuable tool in improving poetry reading skills, offering a more engaging and effective learning experience compared to conventional methods. These results suggest that integrating digital tools, such as videos, animations, and interactive applications, can help students develop better expression, comprehension, and fluency in poetry reading. Future research is recommended to explore different types of interactive media and their long-term impact on literature learning.